Health in Africa (Nature Communications, 2024)
Africa is undergoing a demographic transition1 that has led to significant reductions in the number of individuals living in extreme poverty, and to positive shifts in related health outcomes, across its diverse populations2. Building on these successes requires a consideration of intersecting factors that impact health metrics, which is the focus of the United Nations Sustainable Development Goals3. To support researchers in their efforts towards reaching these goals, Nature Communications, Communications Medicine and Scientific Reports invite submissions of papers that advance our understanding of all aspects of health in Africa.